2017
DOI: 10.1136/bjsports-2016-097210
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary time in older adults: a critical review of measurement, associations with health, and interventions

Abstract: Sedentary time (ST) is an important risk factor for a variety of health outcomes in older adults. Consensus is needed on future research directions so that collaborative and timely efforts can be made globally to address this modifiable risk factor. In this review, we examined current literature to identify gaps and inform future research priorities on ST and healthy ageing. We reviewed three primary topics:(1) the validity/reliability of self-report measurement tools, (2) the consequences of prolonged ST on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
162
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 99 publications
7
162
2
4
Order By: Relevance
“…It is well established that physical activity (PA) is an important factor reducing chronic diseases and fostering a physical, cognitive, and psychosocial healthy aging . In contrast, excessive time spent in sedentary behavior (SED) has been associated with unsuccessful aging and premature mortality, while poor sleep duration and quality have been related to worse health among older people …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that physical activity (PA) is an important factor reducing chronic diseases and fostering a physical, cognitive, and psychosocial healthy aging . In contrast, excessive time spent in sedentary behavior (SED) has been associated with unsuccessful aging and premature mortality, while poor sleep duration and quality have been related to worse health among older people …”
Section: Introductionmentioning
confidence: 99%
“…1 It is well established that physical activity (PA) is an important factor reducing chronic diseases and fostering a physical, cognitive, and psychosocial healthy aging. 2 In contrast, excessive time spent in sedentary behavior (SED) has been associated with unsuccessful aging and premature mortality, 3 while poor sleep duration and quality have been related to worse health among older people. 4,5 Rosenberg et al 6 recently proposed a new paradigm-the 24-hour Activity Cycle-consisting of four basic types of activity (ie, sleep, SED, Light PA [LPA], and moderate-to-vigorous PA [MVPA]) that should be comprehensively assessed over the complete 24-hour period to optimally characterize daily patterns and to understand how they may synergistically affect health.…”
Section: Introductionmentioning
confidence: 99%
“…Second, physical activity, sitting time and the frequency of CAS were assessed using self‐reported questionnaire, which causes recall bias, and might increase the range of error. For example, self‐reported measurement of sitting time generally underestimates the total sitting time among older adults . A systematic review regarding sedentary behavior among older adults reported a large difference in average sedentary time between objective measurement and self‐reported values (9.4 h for objective measurement vs 5.3 h for self‐reported), suggesting that most self‐reported values of sedentary time rather underestimate the actual sedentary time .…”
Section: Discussionmentioning
confidence: 68%
“…For example, self-reported measurement of sitting time generally underestimates the total sitting time among older adults. 29 A systematic review regarding sedentary behavior among older adults reported a large difference in average sedentary time between objective measurement and self-reported values (9.4 h for objective measurement vs 5.3 h for self-reported), suggesting that most self-reported values of sedentary time rather underestimate the actual sedentary time. 4 Therefore, the 6.6 h sitting time reported for the present study population might have been underestimated, distorting the association between sitting time and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation